A New Kind of Iteration Method for Finding Approximate Periodic Solutions to Ordinary Differential Equations (Communications in Mathematical Research, 2021)
In this paper, a new kind of iteration technique for solving nonlinearordinary differential equations is described and used to give approximate periodicsolutions for some well-known nonlinear problems. The most interesting features ofthe proposed methods are its extreme simplicity and concise forms of iteration formulafor a wide range of nonlinear problems.
Keywords: iteration method; approximate periodic solution; ordinary differential equation.